Characterization of the shape-staggering effect in mercury nuclei. Issue 12 (December 2018) - Marsh, B.; Day Goodacre, T.; Sels, S.; Tsunoda, Y.; Andel, B.; Andreyev, A.; Althubiti, N.; Atanasov, D.; Barzakh, A.; Billowes, J.; Blaum, K.; Cocolios, T.; et al.
Abstract In rare cases, the removal of a single proton (Z) or neutron (N) from an atomic nucleus leads to a dramatic shape change. These instances are crucial for understanding the components of the nuclear interactions that drive deformation. The mercury isotopes (Z = 80) are a striking example1, 2 : their close neighbours, the lead isotopes (Z = 82), are spherical and steadily shrink with decreasing N. The even-mass (A = N + Z) mercury isotopes follow this trend. The odd-mass mercury isotopes181, 183, 185 Hg, however, exhibit noticeably larger charge radii. Due to the experimental difficulties of probing extremely neutron-deficient systems, and the computational complexity of modelling such heavy nuclides, the microscopic origin of this unique shape staggering has remained unclear. Here, by applying resonance ionization spectroscopy, mass spectrometry and nuclear spectroscopy as far as177 Hg, we determine181 Hg as the shape-staggering endpoint. By combining our experimental measurements with Monte Carlo shell model calculations, we conclude that this phenomenon results from the interplay between monopole and quadrupole interactions driving a quantum phase transition, for which we identify the participating orbitals. Although shape staggering in the mercury isotopes is a unique and localized feature in the nuclear chart, it nicely illustrates the concurrence of single-particle and collective degrees of freedom at play in atomic nuclei. Spectroscopy and shell model calculations reveal the181 Hg isotope as the endpoint of the shape-staggering of Hg nuclei, a consequence of neutron removal which arises from the interplay of single-particle and collective degrees of freedom.